Implementasi Sistem Filter Air Bersih Sebagai Solusi Penyediaan Air Layak Pakai Pascabencana di Desa Kaseh Sayang - Ade Zulkarnain Hasibuan (LKP KARYA PRIMA KURSUS, 2026)
Flood disasters that occurred in Aceh Tamiang Regency in November 2025 caused a decline in the quality of community clean water sources, particularly in Kaseh Sayang Village. Well water that was previously used for daily needs became turbid, brownish in color, and odorous due to contamination by mud and sediment after the flood. This condition created difficulties for the community in obtaining proper water for daily use. This community service activity aimed to assist the community in gaining access to clean water through the implementation of a simple water filtration system based on layered filtration media. The implementation method consisted of several stages, including identification of clean water problems, coordination with the village government, program socialization, application of water filtration technology, assistance in the use of the technology, and program evaluation. The water filtration technology utilized gravel, silica sand, and activated carbon to filter mud particles and sediments. The results showed that the filtration technology was able to improve the visual quality of water, where previously turbid water became clearer and odorless. In addition, this activity also increased community awareness regarding the importance of clean water management as well as the operation and maintenance of water filtration systems independently.